2020
DOI: 10.1002/jcla.23502
|View full text |Cite
|
Sign up to set email alerts
|

Katanin P60 and P80 in papillary thyroid carcinoma patients: Indicators for exacerbated tumor features and worse disease‐free survival

Abstract: Background This study aimed to explore the clinical implications of katanin P60 and P80 (katanin P60/P80) regarding their correlations with clinicopathological features and survival profiles in papillary thyroid carcinoma (PTC) patients. Methods Tumor tissue and paired adjacent tissue specimens were obtained from 172 PTC patients who underwent lobectomy or thyroidectomy. Besides, immunohistochemistry assay and immunoreactive (IR) score (multiplying staining intensity score by density score) were used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Several studies have shown increased katanin p60 or p80 expression in breast, prostate, and NSCLC tissues separately, [21–26] but the relationship between katanin p60 and p80 expression in these cancers has not been reported. In this study, we also found that katanin p60 levels were positively correlated with katanin p80 levels in PTC, including CPTC and FVPTC, which is consistent with a recently reported study [27] . To further confirm this, we overexpressed katanin p60 in human papillary thyroid carcinoma KTC-1 cells and found that overexpression of katanin p60 significantly increased katanin p80 expression.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Several studies have shown increased katanin p60 or p80 expression in breast, prostate, and NSCLC tissues separately, [21–26] but the relationship between katanin p60 and p80 expression in these cancers has not been reported. In this study, we also found that katanin p60 levels were positively correlated with katanin p80 levels in PTC, including CPTC and FVPTC, which is consistent with a recently reported study [27] . To further confirm this, we overexpressed katanin p60 in human papillary thyroid carcinoma KTC-1 cells and found that overexpression of katanin p60 significantly increased katanin p80 expression.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we also found that katanin p60 levels were positively correlated with katanin p80 levels in PTC, including CPTC and FVPTC, which is consistent with a recently reported study. [ 27 ] To further confirm this, we overexpressed katanin p60 in human papillary thyroid carcinoma KTC-1 cells and found that overexpression of katanin p60 significantly increased katanin p80 expression. As a regulatory subunit, katanin p80 positively regulates the activity of katanin p60.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, in non-small cell lung cancer (NSCLC), the elevated expression of KATNA1 and KATNB1 correlates with lymph node metastasis and advanced tumor progression ( Table 1 ; Wang et al, 2020 ; Ye et al, 2020 ). Katanin expression is also dysregulated in other types of cancers like papillary thyroid carcinoma (PTC), where both KATNA1 and KATNB1 are highly expressed in tumors and tumor-adjacent tissues; furthermore, elevated katanin expression correlates with advanced PTC staging and worse disease-free survival in patients ( Chen et al, 2020 ). The overexpression of katanin subunits in various cancers and findings that activating mutations in katanin contribute to cancer pathogenesis indicate that katanin dysregulation is an important step in tumorigenesis.…”
Section: Katanin Dysfunction In Cancermentioning
confidence: 99%